Search for exclusive rare baryonic decays of B mesons - Coan, T; Fadeyev, V; Korolkov, I; Maravin, Y; Narsky, I; Stroynowski, R; Ye, J; Wlodek, T; Artuso, M; Dambasuren, E; Kopp, S; Moneti, G; et al. (1999)
We report the results of a search for the rare baryonic decay modes B0→ΛΛ̄, B+→Λ̄p, B0→Λ̄pπ-, and B0→pp̄ (and their charge conjugate states) using 5.8 × 106 BB̄ pairs collected with the CLEO detector. We see no statistically significant signals in any of these modes and set 90% confidence level upper limits on their branching fractions, B(B0→ΛΛ̄)<3.9 × 10-6, B(B+→Λ̄p)<2.6 × 10-6, B(B0→Λ̄pπ-)<1.3 × 10-5 and B(B0→pp̄)<7.0 × 10-6. ©1999 The American Physical Society.